2021
DOI: 10.1097/sle.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Scarless Completion Thyroidectomy After Initial Transoral Approach for Differentiated Thyroid Cancer: How and When to Start?

Abstract: Background: With growing literature, the feasibility of transoral endoscopic thyroidectomy vestibular approach (TOETVA) has been confirmed as a valid method for managing differentiated thyroid cancer. Completion thyroidectomy (CT) is recommended in patients who have been diagnosed with differentiated thyroid cancer after unilateral lobectomy by TOETVA. In this retrospective study, the authors addressed the critical questions of how and when to do the second operation of CT to avoid a neck scar. Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Of the studies included in this article, completion thyroidectomy was described by eight studies, using all mentioned techniques except the RA-ET and RA-RT (31,34,41,43,46,57,65,89). Moreover, several other studies described the safety and feasibility of minimally invasive techniques for the completion thyroidectomy, showing the vast range of application of these techniques (65,(120)(121)(122). It is advised to either perform re-operation within two weeks after initial surgery or after two to three months to minimize complications due to adhesions (57,65,120).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies included in this article, completion thyroidectomy was described by eight studies, using all mentioned techniques except the RA-ET and RA-RT (31,34,41,43,46,57,65,89). Moreover, several other studies described the safety and feasibility of minimally invasive techniques for the completion thyroidectomy, showing the vast range of application of these techniques (65,(120)(121)(122). It is advised to either perform re-operation within two weeks after initial surgery or after two to three months to minimize complications due to adhesions (57,65,120).…”
Section: Discussionmentioning
confidence: 99%
“…TOETVA has become an attractive minimally invasive thyroidectomy approach for both surgeons and patients worldwide because it provides excellent cosmetic outcomes (14). TOETVA leaves no visible scars because the intraoral scars are unnoticeable and heal completely within 2 two 3 weeks, compared to other remote-access approaches which merely transfer scars to other parts of the body (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…After 2 weeks, tight adhesion may pose difficulty in opening the space again. Wu et al [ 65 ] proposed creating a working space through a different approach if completion thyroidectomy was performed beyond 2 weeks. Anuwong et al [ 18 ] suggested postponing the surgery 6 months later if a repeated transoral approach is desired.…”
Section: Special Considerationmentioning
confidence: 99%